The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.juro.2012.07.101
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Urethroplasty After Failed Urethral Reconstruction: Outcome Analysis of 130 Patients

Abstract: Purpose Male urethral stricture disease accounts for a significant number of hospital admissions and health care expenditures. Although much research has been completed on treatment for urethral strictures, fewer studies have addressed the treatment of strictures in men with recurrent stricture disease after failed prior urethroplasty. We examined outcome results for repeat urethroplasty. Materials and Methods A prospectively collected, single surgeon urethroplasty database was queried from 1977 to 2011 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 18 publications
3
44
1
3
Order By: Relevance
“…18 Repeat urethroplasty is a viable option for stricture recurrence. 15 In the 20% of our urethroplasties having undergone previous repair, we found that previous urethroplasty does not contribute to treatment failure.…”
Section: E299mentioning
confidence: 60%
See 1 more Smart Citation
“…18 Repeat urethroplasty is a viable option for stricture recurrence. 15 In the 20% of our urethroplasties having undergone previous repair, we found that previous urethroplasty does not contribute to treatment failure.…”
Section: E299mentioning
confidence: 60%
“…Lichen sclerosus has been implicated with failure after repeat urethroplasty; we believe that the reason for recurrence is that the underlying disease has not been adequately treated such that it is not truly treatment failure, but rather disease progression as part of the natural history of Lichen sclerosus. 15,16 Infectious etiology is another risk factor for recurrence. These strictures are secondary to Reiter's syndrome or Fournier's gangrene where significant tissue inflammation and necrosis may occur.…”
Section: Discussionmentioning
confidence: 99%
“…6972 Studies have also shown excellent success rates for redo urethroplasty (78% in one large series). 73 Predictors of failure following repeat urethroplasty include a history of hypospadias repair, lichen sclerosis, and a history of two or more failed prior urethroplasties. 74 …”
Section: Managementmentioning
confidence: 99%
“…These outcomes are similar to those in previous reports of the success of salvage EPA for bulbar recurrences. 5 It is important to note that in the series by Siegel et al the cohort of men undergoing salvage EPA was selective and limited to those with relatively short segment bulbar disease without more complex urethral pathology caused by LS, previous pelvic radiation treatment, pelvic fracture related urethral injury or previous hypospadias surgery. 9 In patients with complex urethral pathology and stricture recurrence a thoughtful approach toward surgical management is needed as many have deficient and diseased genital skin, extensive scar tissue, obliterated tissue planes and a tenuous urethral blood supply.…”
mentioning
confidence: 99%
“…Despite the risk of reconstructive failure in these patients salvage urethroplasty in experienced hands offers recurrence-free outcomes (defined as no further need for postoperative instrumentation) as high as 79% along with significant improvement in patient reported satisfaction with surgery and quality of life. 5,10 Penile urethroplasty carries a higher risk of recurrent stricture than bulbar urethroplasty in primary and salvage cases. 1,10 Many men with a recurrent stricture after urethroplasty have significant genital skin deficiency, a lengthy stricture, LS or severe spongiofibrosis.…”
mentioning
confidence: 99%